PREVALENCE OF MICROALBUMINURIA IN UNTREATED NIGERIAN HYPERTENSIVE PATIENTS - TALLE MA; OKEAHIALAM BN; BAKKI B; GEZAWA ID; BUBA F; BABA MM; ABDUL H; GONI BW (Ntec Specialist, 2010)
Background: The burden of cardiovascular disease imposed by hypertension is a result of target organ damage. Microalbuminuria (MA) is the first clinical expression of nephropathy and has become a cardiovascular and/or renal disease prognostic indicator for hypertensive subjects. Objectives: To establish the prevalence of MA among newly diagnosed hypertensive patients using the simple spot urine Albumin-Creatinine Ratio (ACR). Method : One hundred and eighty six newly diagnosed hypertensive patients were enrolled for assessment of MA using spot urine ACR. Those with overt proteinuria, diabetes mellitus, overt kidney disease and other potential causes of albuminuria were excluded. Spot urine was obtained for measurement of albumin and creatinine. Anthropometric variables were measured and body mass index calculated. All patients had echocardiographic assessment. Statistical analysis was performed using SPSS version 11.0 software. Multiple regression analysis was used in determining predictors of MA. A p-value of ≤ 0.05 was considered significant. Results: Results of 136 patients comprising of 66(48.53%) males and 70(51.47%) females was considered. The overall prevalence of microalbuminuria was 42.65%. Males had a prevalence of 51.52% compared to 34.27% for the females (p=0.29). Weight, BMI, LVM, LVMI, UAE, and ACR were significantly higher in patients with MA, whereas those without MA had a significantly higher urinary creatinine. Multiple regression analysis identified DBP, MAP, LVM and LVMI as significant predictors of increased urinary albumin excretion. Microalbuminuria showed significant positive correlation with LVM and LVMI. Conclusion: The prevalence of microalbuminuria is high among untreated Nigerian hypertensive patients. The spot urine ACR provides a simple, accurate and cost effective way of identifying this high risk group of hypertensive patients, allowing for more aggressive treatment to reduce cardiovascular outcomes